Relationship between transformational leadership and personality with the commitmment to the organisation (Case study at food and drugs administration republic of Indonesia) - Ratno . (The Management Journal of Binaniaga, 2020)
The purpose of this study is to study whether there is a relationship between Transformational Leadership and Personality with the coommitment to Organization both partially and simultaneously. The population of this study are head office employees which is 1,413 employees. The formula determines the number of samples based on Slovin, after the calculation, it is obtained a sample of 312 samples. The research instrument is a questionnaire. The collected data are tested by using correlation analysis techniques. The results has showed that: 1. Transformational leadership partially relates to the commitment to the organization, 2. Partial personality has related to the commitment,to the organization 3. Transformational leadership and personality simultaneously correlate positively to the commitment organization having the ratio of 0.770, then the functional relationship is obtained by equation = 27,589 + 0,725X1 + 0,17 X2 and the coefficient of determination or contribution of transformational leadership and personality simultaneously to the commitment to the organization is 59,3%. Keywords: Transformational Leadership, Personality and Commitment to Organizations.